2018
DOI: 10.1111/jne.12614
|View full text |Cite
|
Sign up to set email alerts
|

Participation of membrane progesterone receptor α in the inhibitory effect of progesterone on prolactin secretion

Abstract: The membrane progesterone receptors (mPRα, mPRβ, mPRγ, mPRδ and mPRε) are known to mediate rapid nongenomic progesterone functions in different cell types. However, the functions of these receptors in the pituitary have not been reported to date. In the present study, we show that the expression of mPRα was the highest among the mPRs in the rat anterior pituitary gland. Immunostaining of mPRα was detected in somatotrophs, gonadotrophs and lactotrophs. Interestingly, 63% of mPRα-positive cells within the pituit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 51 publications
(85 reference statements)
0
11
0
Order By: Relevance
“…Since the upregulated expression of immunosuppressive protein PD-L1 was observed in the pituitary gland of PA patients [43], the inhibition of LMO4/STAT3/PD-L1 signaling could block the immune evasion by recovering the recognition and elimination of cancer cells via CD8 + lymphocytes [48]. Furthermore, the transforming growth factor-beta ( TGFB ) was reported to be one of the chief immune suppressive mediators of PRL secretion and PA proliferation [49,50]. Its receptor, TGFBR3 , was also discovered in this study as a DEG, which could be another target candidate for developing novel PA immunotherapy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the upregulated expression of immunosuppressive protein PD-L1 was observed in the pituitary gland of PA patients [43], the inhibition of LMO4/STAT3/PD-L1 signaling could block the immune evasion by recovering the recognition and elimination of cancer cells via CD8 + lymphocytes [48]. Furthermore, the transforming growth factor-beta ( TGFB ) was reported to be one of the chief immune suppressive mediators of PRL secretion and PA proliferation [49,50]. Its receptor, TGFBR3 , was also discovered in this study as a DEG, which could be another target candidate for developing novel PA immunotherapy.…”
Section: Resultsmentioning
confidence: 99%
“…Increased levels (both mRNA and protein) of programmed death-ligand 1 ( PD-L1 , the immunosuppressive protein) are observed in tumor tissue of PA patients [43], which can induce immune evasion by desensitizing the recognition and elimination of cancer cells via CD8 + lymphocytes [48]. Transforming growth factor-beta ( TGFB ) was discovered as one of the chief immune suppressive mediators of prolactin (PRL) secretions and PA proliferation [49,50]. Apart from the above studies, a variety of transcriptomics analyses (demonstrated in Table 1) have been conducted to identify the differentially expressed genes (DEGs) between PA patients and normal ones [51,52,53,54].…”
Section: Introductionmentioning
confidence: 99%
“…mPRs mediate rapid, non-classical progesterone actions, which are frequently non-genomic, by activating G proteins and modulation of intracellular signaling pathways. The five mPR members of the PAQR family, mPRα (PAQR7), mPRβ (PAQR8), mPRγ (PAQR5), mPRδ (PAQR6), and mPRε (PAQR9), have different tissue distributions, progestin binding (32,33), relaxation of human myometrial and vascular muscle cells (34,35), reversal of epithelial to mesenchymal transition in breast cancer cells (36), and inhibition of prolactin release from rat lactotrophs through activation of TGFβ1 (37).…”
Section: Membrane Progesterone Receptors (Mprs Paqrs)mentioning
confidence: 99%
“…mPRα is the predominant mPR isoform expressed in most progesterone target tissues with the exception of the brain and is the primary mPR that regulates several critical reproductive and non-reproductive progestin functions. For example, mPRα mediates oocyte meiotic maturation and sperm motility in fish, anti-apoptosis in fish ovarian granulosa cells and in human breast cancer cells ( 32 , 33 ), relaxation of human myometrial and vascular muscle cells ( 34 , 35 ), reversal of epithelial to mesenchymal transition in breast cancer cells ( 36 ), and inhibition of prolactin release from rat lactotrophs through activation of TGFβ1 ( 37 ).…”
Section: Membrane Progesterone Receptors (Mprs Paqrs)mentioning
confidence: 99%
See 1 more Smart Citation